Fostering community-based water quality and quantity monitoring through citizen science in the Ashanti Region of Ghana: a citizen science training report - Adusei-Gyamfi, J.; Gyebi, A. S. A.; Amponsah, Andoh Kwaku; Atampugre, Gerald; Tilahun, Seifu A.; Cofie, Olufunke O. (International Water Management Institute (IWMI). CGIAR Initiative on West and Central African Food Systems Transformation, 2023)
Citizen Science (CS) is increasingly being integrated into advanced scientific approaches to address complex problems and produce real-time evidence-based information for decision-making. The CS approach has also been used as a tool to foster community-based monitoring and learning, particularly on the sustainability of productive landscapes/watersheds. As part of the CGIAR regional initiative, West and Central African AgriFood Systems Transformation (TAFS-WCA), the International Water Management Institute (IWMI) trained seven (7) citizen scientists (CSs) in communities in and around the Mankran watershed in the Ahafo-Ano Southwest District (AASWD) in Ashanti Region of Ghana for a one-year intensive hydrological monitoring campaign. Researchers from IWMI and the Kwame Nkrumah University of Science and Technology (KNUST) conducted a kick-off stakeholder engagement to initiate the program, recruited local volunteer citizen scientists, co-identified monitoring stations, and co-installed field equipment. This was followed by a CS training workshop aimed at enhancing CSs' understanding of hydrology and water quality assessments. An evaluation of the perception of the CSs before the training revealed that most of them are not first-time volunteers, as three of them volunteer at least once a month for varied purposes. Although none have ever volunteered for any water research projects, most agree that they would be personally affected if the quality of the environment deteriorates. Knowledge acquisition was the driving force for participation, with one participant motivated by financial or unemployment reasons. A follow-on trend analysis will be performed after one year to assess the evolution of CSs perception. The training program proved to be an exceptional journey of immense significance for the CSs and the researchers applying the CS approach. Through a series of hands-on activities and practical exercises, CSs were equipped with skills in water sampling and quality monitoring, operating and maintenance of scientific instruments, and accurate data collection to build indigenous competent volunteers who inspire behavioral change and enhance environmental stewardship and active citizenship for the successful implementation of an inclusive landscape management plan.